Change in clinical presentation at admission in children with newly diagnosed type 1 diabetes during the COVID-19 pandemic in the eastern region of Turkey (Annals of Medical Research, 2022)
Aim: The COVID-19 pandemic is a global health problem with high morbidity and mortality. This study aimed to compare the clinical features of newly diagnosed type 1 diabetes (T1D) patients during the pandemic with those diagnosed earlier and evaluate how the pandemic affected the T1D clinical findings on admission.Materials and Methods: This is a 2-year, single-center, cross-sectional study. The time between March 11, 2019, and March 11, 2020, was defined as the “pre-pandemic period,” while the interval between March 11, 2020, and March 11, 2021, was called the “pandemic period.” The clinical and laboratory parameters of newly diagnosed T1D patients admitted in these two time periods were compared.Results: The admission rate with DKA was higher in the pandemic period than in the pre-pandemic time (71.0% and 52.8%, respectively, p=0.046). There was no difference between the groups regarding the severity of DKA. The mean duration of diabetes symptoms before diagnosis was longer during the pandemic than in the pre-pandemic period (17.0 days and 12.5 days, respectively, p=0.035).Conclusions: Delayed admissions to health institutions of patients with diabetes signs and symptoms during the pandemic are worrisome. This delay is likely to have increased the DKA rate during the pandemic. As a result, children with diabetes symptoms should be ensured to apply to a health institution without hesitation, even in the pandemic.
Keywords: COVID-19 pandemic; Diabetic ketoacidosis; Type 1 diabetes mellitus; Childhood